If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 61 = 90 Reorder the terms: 61 + x = 90 Solving 61 + x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-61' to each side of the equation. 61 + -61 + x = 90 + -61 Combine like terms: 61 + -61 = 0 0 + x = 90 + -61 x = 90 + -61 Combine like terms: 90 + -61 = 29 x = 29 Simplifying x = 29
| -6y+1=-17 | | 4x-9=1.25x-.75 | | x(2.4x)=979 | | 9x+72=4x+108 | | 14x^2-13x+c=0 | | 5(0.3x+0.1y)0.2x= | | 2(x-8.00)=14.00 | | c*6=3 | | (2x-3)=9 | | 3x+89=180 | | -13n=-13 | | 2(2x+1)=x+17 | | 5a^2+3b^3=0 | | 7(x+3)=2y+25 | | 8u-4=4u+40 | | 84-7n= | | 3(2+6)=18b | | 4y(3-6)+3y= | | -2x^2-100=0 | | 17x^2-14x-20=0 | | u^2-2uv-63v^2= | | 5a^2-3b^3=0 | | (2x+6)=146 | | 3x-20=5x+12 | | 3*X=7 | | 9n-4.5= | | 55+0.25x=45+0.10x | | 4x+61+67-3x+x+74=180 | | 17x^2+48x-14=0 | | .75t-.625=.5t-.25 | | 17x^2=48x-14 | | 0.5+3n= |